Heritability and correlation of yield and quality traits in durnm wheat (Triticum Durum) - YAGD, KOKSAL; SOZEN, ELIF; CIFCI, ESRA AYDOGAN (The Indian Journal of Agricultural Sciences, 2011)
A study was carried out during 2001-2005 to determine the inheritance of agronomical and quality traits and correlations between the traits in durum wheat (Triticum dururn Desf.). The environment variance was significant for seedslspike, 1 000-kernel weight, seed weightlspike and test weight (hectolitre mass). Plant height, spike length, spikeletsl spike and test weight showed significant genotypic variance. For seed yield, sedimentation and protein content were found significant in both years and genotype x environment variance component. Gluten content showed significance in both genotypes and genotype x environment interaction. Protein content had the lowest broad sense heritability value (2.08 %),where& spike length had the highest (35.48 96). Heritability values were 9.07,15.01, 2.97,3.0,9.22 and 5.61 % for plant height, spikeletslspike, seedslspike, seed weight/spike, 1 000-kernel weight and seed yield respectively. The gluten content had the highest heritability (25.82 %), followed by sedimentation (13.89 %) and test weight (10.67 %) in quality traits. Significant positive correlation was found between seed yield and plant height (0.39) and plant density (0.29). Negative and significant correlations were found between test weight and plant density (-0.62), seed yield (-0.44), gluten content and seeddspike (-0.20), seed weight/ spike (-0.23), sedimentation and spike length (-0.21), spikeletsl spike (-0.19) , seeddspike (-0.25), protein content and seeddspike (-0.31) and seed weightlspike (-0.20).